Easy tools to screen Italian women suffering from migraine with and without aura in early reproductive age. (November 2019) - Grandi, Giovanni; Imbrogno, Maria Giovanna; Cainazzo, Maria Michela; Pini, Luigi Alberto; Baraldi, Carlo; Guerzoni, Simona; Nappi, Rossella Elena; Facchinetti, Fabio
Abstract: Objective: Early diagnosis of migraine with (MA)/without aura (MO) is vitally important to prevent adverse events during combined hormonal contraceptive (CHC) use and to provide personalized surveillance programs during pregnancy. The aim of this study is to provide clinicians with simple and fast tools to diagnose MO and MA in daily clinical practice. Study design: This study was based on a questionnaire to women of early reproductive age (18–35 years old) then randomized to undergo a neurological consultation. The ID-migraine questionnaire (PIN) and visual aura rating scale (VARS) were used. Results: A total of 240 subjects were included in the study, with a total prevalence of MO diagnosed by PIN of 67.0% of subjects with headache, 49.2% of the total study population, and of MA by VARS of 12.5% subjects with headache, 9.2% of the total study population. Eighty-seven neurological examinations were randomly performed: PIN showed a sensitivity of 85.7% (95% CI 75.3%–92.9%) and a specificity of 52.9% (95% CI 27.8%–77.0%), while VARS displayed a sensitivity of 100.0% (95% CI 69.2%–100.0%) and a specificity of 45.5% (95% CI 16.8%–76.6%). Conclusion: High sensitivity, in particular for the presence of MA, associated with low specificity suggest that PIN and VARS questionnaires can be effective tools to identify those young patients who require specific neurological examinations in view of the prescription of a CHC or pregnancy planning.